2008
DOI: 10.1002/jnr.21872
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of nitrated brain proteins in traumatic brain‐injured rats treated postinjury with gamma‐glutamylcysteine ethyl ester: Insights into the role of elevation of glutathione as a potential therapeutic strategy for traumatic brain injury

Abstract: Traumatic brain injury (TBI) occurs suddenly and has damaging effects to the brain that are dependent on the severity of insult. Symptoms can be mild, moderate, or severe. Oxidative damage is associated with traumatic brain injury through reactive oxygen/nitrogen species production. One such species, peroxynitrite, is elevated in TBI brain tissue (Orihara et al. [2001] Forensic Sci. Int. 123:142-149; Deng et al. [2007] Exp. Neurol. 205:154-165). Peroxynitrite can react with carbon dioxide and decompose to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…The radical scavenging abilities of the essential oil could be linked to the presence of phenolic monoterpenes 50 . Although, Aazza et al 51 showed that some of the essential oil components of lemon peels as revealed by this study such as α-pinene, b-pinene, limonene, linalool, 1,8-cineole, linalyl acetate and borneol had less than 50 DPPH* scavenging ability, the observed radical scavenging ability of the essential oils used in this study could be a result of synergistic effect of the volatile constituents Figure 5D showed that the essential oil had a dose-dependent Fe 2 chelating ability with EC 50 value of 133.5 μL/ L. Iron plays an important role in the generation of hydroxyl radicals 52 and also in the development of neurodegenerative conditions as it accumulates in the brain of patients with Alzheimer s disease 53 . The ferric reducing antioxidant property and Fe 2 chelating ability of the citrus peel essential oil could therefore be beneficial in the management/ prevention of neurodegenerative conditions.…”
Section: Antioxidant Activitymentioning
confidence: 70%
“…The radical scavenging abilities of the essential oil could be linked to the presence of phenolic monoterpenes 50 . Although, Aazza et al 51 showed that some of the essential oil components of lemon peels as revealed by this study such as α-pinene, b-pinene, limonene, linalool, 1,8-cineole, linalyl acetate and borneol had less than 50 DPPH* scavenging ability, the observed radical scavenging ability of the essential oils used in this study could be a result of synergistic effect of the volatile constituents Figure 5D showed that the essential oil had a dose-dependent Fe 2 chelating ability with EC 50 value of 133.5 μL/ L. Iron plays an important role in the generation of hydroxyl radicals 52 and also in the development of neurodegenerative conditions as it accumulates in the brain of patients with Alzheimer s disease 53 . The ferric reducing antioxidant property and Fe 2 chelating ability of the citrus peel essential oil could therefore be beneficial in the management/ prevention of neurodegenerative conditions.…”
Section: Antioxidant Activitymentioning
confidence: 70%
“…6,7 Furthermore, studies have shown that high amounts of lipid peroxidation products such as malondialdehyde (MDA) and hydroxynonenal are present in the brains of Alzheimer's disease patients. 8,9 The inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzyme activities is a modern therapeutic approach to the management of neurodegenerative conditions such as Alzheimer's disease. 4 The inhibition of these enzymes leads to increased communication between nerve endings and increased activities in the cholinergic pathways in the brain, thereby alleviating the symptoms of Alzheimer's disease.…”
mentioning
confidence: 99%
“…The combination of high polyunsaturated fatty acid content, high oxygen respiration and glucose metabolism, and relatively low antioxidant capacity in the brain establishes an environment that is highly susceptible to oxidative stress. Thus, because the brain is not adequately prepared to defend against the almost immediate surge of reactive oxygen species (ROS) formation that is brought about by a traumatic brain injury (TBI), utilizing the native antioxidant mechanisms of the brain by increasing glutathione availability is a treatment route whose ability to curb initial inflammatory processes in the brain appears very promising [94,95]. Synthesis of glutathione, illustrated in Figure 9, occurs in a two-step mechanism where glutamate and cysteine are first covalently bound via γ-linkage to produce γ-glutamylcysteine (γ-GC) by the enzyme γ-glutamylcysteine synthetase, and then glycine is covalently bound to γ-GC via α-linkage to cysteine by the enzyme glutathione synthetase.…”
Section: Gamma-glutamylcysteine Ethyl Estermentioning
confidence: 99%
“…In fact, intracerebroventricular administration of γ-GC increases brain glutathione content more so than intracerebroventricular administration of GSH ethyl ester or intraperitoneal administration of cysteine in rats [96]. The γ-GC analog, γ-glutamylcysteine ethyl ester (GCEE), shown in Figure 9B, has also proven to be an excellent candidate for supplementing intracellular γ-GC availability by increasing glutathione concentrations, and has been shown to decrease markers of oxidative stress both in vitro and in vivo [95,[97][98][99].…”
Section: Gamma-glutamylcysteine Ethyl Estermentioning
confidence: 99%